Eleições sob ditaduras: São Tomé e Príncipe antes e após a independência - Nascimento, Augusto (Africana Studia, 2020)
This text aims to highlight the differences and continuities of the electoral exercise under the colonialist dictatorship and, after independence, under the one-party regime in São Tomé and Príncipe. The non-adoption of democracy at independence in 1975 was not due to inexperience with democratic procedures caused by a dictatorial character of colonialism. By contrast, the failure to hold free and competitive elections was a reserved choice of the new leaders whose aim was to achieve and preserve power, if necessary against the will of the people whose interests they claimed to be defenders. Under dictatorships, the formalities of the elections – or, strictly speaking, their simulacrum – were meant to aid the fiction of the legitimation of dictatorial colonial power and the single post-independence party. Both regimes bet on forcibly obtaining the consent or consent of the governed.